A Rare Complication of Central Venous Catheter Extravasation in a Preterm Neonate: Hemidiaphragmatic Paralysis - Hobson, C. (AJP Rep, 2017)
We report a case of a preterm neonate born at 26 weeks' of gestation diagnosed with unilateral diaphragmatic paralysis. This paralysis was a consequence of a phrenic nerve injury due to extravasation of hyperosmolar parenteral nutrition fluid in the upper thorax. Chest X-rays and ultrasonography confirmed the diagnosis. The neonate was treated with prolonged respiratory support and did not require surgical treatment. This report describes a case of hemidiaphragmatic paralysis as a complication of central venous catheter insertion. In neonates, spontaneous recovery of diaphragmatic paralysis is possible. This study concludes that recovery of extravasation injury-induced phrenic nerve palsy in the context of conservative management is possible.